The Existence of Crypto Currency as a Currency and Investment Asset inthe Perspective of Islamic Economic - Naurun Nisa; Samsahudi Samsahudi; Wildan Wildan (Yayasan Rahmat Islamiyah, 2026)
This research aims to observe Cryptocurrency which has recently been in great demand because it has advantages such as being safe from high inflation, low transaction costs and its value quickly soaring, but so far crypto money does not have a real physical form so researchers want to see how the existence of Cryptocyrenccy as a currency and investment asset in the perspective of Sharia economics the method used is a qualitative method, namely by conducting research with direct observation that is interactive and presenting the results of the research according to the data obtained. The author uses a descriptive qualitative approach, namely by collecting, compiling, and describing various documents, actual information data that aims to describe a situation being studied; The existence of cryptocurrency both as a currency and as an investment asset when viewed from an Islamic economic perspective can be said to be gharar because the intrinsic elements have not been fulfilled both from physical form, value, having a definite amount of value, ownership rights and can be handed over to the buyer.